Chinese immigrants in network marketing business in western host country context - Dai, F.; Wang, K.; Teo, Stephen (Elsevier Science Ltd, 2011)
Many Chinese immigrants start their entrepreneurship business by joining major network marketing businesses in Western host countries. The willingness of these Chinese immigrants to undertake network marketing rests on the influence of the social environment of the network marketing organization. Network marketing specific self-efficacy, social competence and motivation for establishing one’s own business are also hypothesized to play an important role in their engagement in entrepreneurial actions. Drawing upon Bandura’s social cognitive theory and the immigrant entrepreneurship literature, the present study investigates whether the social environmental influence of a network marketing organization affects the extent to which Chinese immigrants develop the self-efficacy, social competence and motivation to establish their own business and how these variables affect the actions undertaken in the host country. The study is based on the sample of 194 Chinese immigrants in their adopted host country, Australia. The findings of the survey suggest that the social environment within network marketing organizations positively affects self-efficacy, which in turn positively affects the entrepreneurial actions undertaken by Chinese immigrants in conducting their network marketing business. Social environmental influence impacts positively on their motivation to establish their own network marketing business and social competence. However the effects of motivation and social competence on entrepreneurial action were not supported. Theoretical and managerial implications are discussed.